Catalytic pyrolysis of corn straw fermentation residue for producing alkyl phenols. (August 2017) - Wang, Ze; Dang, Dan; Lin, Weigang; Song, Wenli
Abstract: Phenolic-oil can be upgraded by etherification with methanol to decrease the polarity and acidity of the product oil. However, alkoxy phenols have an inhibiting effect to the etherification of alkyl phenols in the phenolic mixture. So, it is very important to produce alkyl phenols with high selectivity and extremely low content of alkoxy phenols, through a catalytic pyrolytic process. Herein, the effects of HZSM-5, NaY, and KH2 PO4 /AA (KH2 PO4 loaded on activated Al2 O3 ) on the pyrolysis of corn straw fermentation residue are investigated, for producing alkyl phenols high efficiently. KH2 PO4 /AA is found to be the best catalyst in promoting the formation of alkyl phenols and in inhibiting alkoxy phenols. Under the catalysis of KH2 PO4 /AA, the tar yield increases with rising temperature, and reaches to the maximum tar yield of 13.7% at 500 °C, and then declines with further increasing temperature. The tar obtained under optimized reaction conditions, nearly consists of 50% of alkyl phenols and over 23% of aliphatic hydrocarbons with zero content of alkoxy phenols. K3 Al2 (PO4 )3 is generated from the solid phase reaction between KH2 PO4 and Al2 O3, through which alkoxy phenols can be high selectively adsorbed and activated, and thus leads to the formation of alkyl phenols. Highlights: KH2 PO4 /AA can effectively promote the conversion of alkoxy phenols to alkyl phenols. A maximum tar yield of 13.7% under catalysis of KH2 PO4 /AA appeared at 500 °C. In best results, the tar consists of 50% of alkyl phenols with little alkoxy phenols. Selective adsorption of alkoxy phenols on K3 Al2 (PO4 )3 is critical to the catalysis.